2008
DOI: 10.1093/humrep/den180
|View full text |Cite
|
Sign up to set email alerts
|

A new LH receptor splice mutation responsible for male hypogonadism with subnormal sperm production in the propositus, and infertility with regular cycles in an affected sister

Abstract: LHR mutations may represent an underestimated cause of infertility in women, in addition to being responsible for male hypogonadism with reduced spermatogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 21 publications
2
34
0
Order By: Relevance
“…Hormones exert their biological effects through binding with their receptors. The male carriers of homozygous mutation of the LHR gene display delayed puberty, micropenis, and oligospermia, so LHR mutations may be responsible for male hypogonadism with reduced spermatogenesis (Bruysters et al, 2008). Gonadotropins and androgen receptors (AR) play a role in gonadal development (Omran Nel, 2012), and FSH and testosterone are the main hormonal regulators of spermatogenesis (Sofikitis et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Hormones exert their biological effects through binding with their receptors. The male carriers of homozygous mutation of the LHR gene display delayed puberty, micropenis, and oligospermia, so LHR mutations may be responsible for male hypogonadism with reduced spermatogenesis (Bruysters et al, 2008). Gonadotropins and androgen receptors (AR) play a role in gonadal development (Omran Nel, 2012), and FSH and testosterone are the main hormonal regulators of spermatogenesis (Sofikitis et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Mutations that lead to loss-offunction in the male are linked with severe phenotypes, such as female external genitalia, micropenis and oligospermia; while in women primary and secondary sexual characteristics develop normally, but infertility is common [131,132]. Bruysters and colleagues have recently described a family that carries a homozygous mutation G→A at position -1 at the intron 10/exon 11 boundary of the LHR gene, resulting in alternative splicing of LHR and an F o r R e v i e w O n l y eight amino acid deletion [53]. In vitro studies have shown that receptor expression is not affected, but the potency of LH (but not human chorionic gonadotropin) is reduced; thus, this LHR isoform shows impaired hormone responsiveness [53].…”
Section: Alternative Splicing Of Gpcrs In Reproductionmentioning
confidence: 99%
“…Bruysters and colleagues have recently described a family that carries a homozygous mutation G→A at position -1 at the intron 10/exon 11 boundary of the LHR gene, resulting in alternative splicing of LHR and an F o r R e v i e w O n l y eight amino acid deletion [53]. In vitro studies have shown that receptor expression is not affected, but the potency of LH (but not human chorionic gonadotropin) is reduced; thus, this LHR isoform shows impaired hormone responsiveness [53]. A male patient and his three sisters showed reproductive impairment.…”
Section: Alternative Splicing Of Gpcrs In Reproductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific importance of LH activity can be demonstrated in patients with LHβ or LH receptor gene mutations. Case reports of these male and female patients have demonstrated hypogonadism, infertility, pseudohermaphroditism, and amenorrhea (11)(12)(13). In assisted reproduction technologies (ART), the importance of LH is demonstrated clearly in hypogonadotropic hypogonadic patients.…”
Section: Introductionmentioning
confidence: 99%